The impact of work alienation on organizational citizenship behavior in the Canary Islands - Jess SurezMendoza, Mara; ZoghbiManriquedeLara, Pablo (International journal of organizational analysis (2005), 2007)
Purpose - The purpose of this research is to examine work alienation (WA) as a mediator in the relationship between employees' perceptions of person-organization (PO) fit - operationalized as value congruence - and organizational citizenship behavior (OCB) directed at their organization (OCBO), co-workers (OCBIC), and students or clients (OCBIS).Design methodology approach - Data were collected from 99 of the 156 (63.5 percent) teachers at a district high school in Spain. Structural equation modeling (SEM) was used to test the predicted relationships.Findings - Results support that PO fit is an antecedent of OCBO, OCBIC, and OCBIS and also, in general, that the three dimensions of WA (powerlessness, meaninglessness, and self-estrangement) mediate this link. Separately, all WA dimensions are totally or partially supported as "full mediators," except for powerlessness and meaninglessness that appear to act on OCBIS as "partial mediators." The model tested suggests PO fit predicts OCB and that this relationship can be explained by the mediating role of WA.Research limitations implications - Subjects in this study reflect job conditions peculiar to the public sector. This may limit the ability to extrapolate the findings to the private sector. Also, results may not generalize to other cultural or national contexts. The findings contribute to an improved understanding of the influence of PO value fit misfit on OCB.Practical implications - Understanding how PO fit is able to affect citizenship behavior suggests that actions designed to promote PO fit may be useful for more efficiently managing employee WA, and, therefore, more powerfully eliciting OCB in the workplace.Originality value - Employee work alienation is demonstrated to be a mediator in the relationship between PO fit and OCB. This is the first empirical test of this relationship.